Properties of Short-Period Internal Waves in the Kara Gates Strait Revealed from Spaceborne SAR Data - Kopyshov Ilya; Kozlov Igor; Shiryborova A.; Myslenkov Stanislav (Russian Journal of Earth Sciences, 2023)
This paper presents the results of identification of surface manifestations (SM) of short-period internal waves (SIW) in Sentinel-1 A/B synthetic aperture radar (SAR) images of the Kara Gates Strait in August–September 2021. 44 SM of SIW trains were detected in 47 SAR images. Statistics of occurrence, propagation direction and spatial characteristics of SIWs in the study area are given. During two months, satellite observations cover almost all phases of spring-neap tidal cycle. The use of a detailed topography of the study area made it possible to identify certain regions with a more frequent presence of the SIW leading crests with a particular focus made on the shallow (< 100 m) part of the strait. Each identified region is then described in terms of water depth, dimensionless slope, amplitudes of tidal current velocity and properties of SIWs. The obtained results were then compared with the results of previous studies.